Trophic state of the Tanjung Putus Lake, based on Nygaard Index - Eko Simatupang; Asmika H. Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT   Nygaard Index can be used to determine the trophic state of waters. Calculation of this index is based on the number of phytoplankton species in these following groups, namely Desmidiaceae, Myxophyceae, Chlorococcales, Centric diatom and Euglenophyceae. To understand the trophic state of the Tanjung Putus lake, a research has been conducted in February - March 2018. There were three sampling stations, namely station 1 (inlet area), station 2 (the middle of the lake) and station 3 (out let area). In each station there were two sampling points, in the surface and 2 secchi depth. Sampling were conducted 3 times, once/week. Water quality parameters measured were phytoplankton (type and abundance), transparency, temperature, pH, nitrate, phosphate, Dissolved oxygen and free carbon dioxide. Results shown that there were 6 groups of phytoplankton present, namely Desmidiaceae (6 species), Myxophyceae (3 species), Chlorococcales (9 species), Centric diatom (5 species), Cryptophyceae (2 species) and Euglenophyceae (2 species). Water quality parameters were as follows: transparency 77.5-102.5 cm, temperature 30-32 0C, pH 5, nitrate 0.04-0.07 mg/L, phosphate 0.03-0.09 mg/L, Dissolved oxygen 4.1-6.5 mg/L, free carbon dioxide 6.6-11.9 mg/L, Nygaard Index value : 2 – 2.6. Based on Nygard Index, the trophic state of the Tanjung Putus Lake can be categorized as mesotrophic to eutrophic. Keywords: Nutrient, Phytoplankton, Mesotrophic, Eutrophic